User Experience Analysis of MyPertamina Application Using User Experience Questionnaire (UEQ) and System Usability Scale (SUS) - Sakdiah, Gewik; Ahsyar, Tengku Khairil; Megawati, Megawati; Angraini, Angraini (APIC, 2025)
MyPertamina is a digital wallet application developed by PT Pertamina (Persero) to facilitate cashless fuel payments and offer loyalty programs. Despite exceeding 10 million downloads, the application received a 3.3 rating on Google Play Store as of May 2023, indicating user complaints. This study analyzes the user experience of the MyPertamina application using the User Experience Questionnaire (UEQ) and System Usability Scale (SUS). Respondents were active users selected purposively through online questionnaires. The study results show all UEQ dimensions scored within the neutral range, with the highest score on Perspicuity (mean 0.453) and the lowest on Novelty (mean -0.068). SUS measurements place the application in the Marginal Low category under acceptability ranges and grade D in the grade scale, indicating significant room for improvement. However, the application received a ”Good” rating in the adjective rating category, reflecting its utility despite suboptimal performance. In conclusion, the MyPertamina application requires enhancements to meet user expectations and improve overall user experience